AB0504 HTR2A Polymorphisms Influence in Systemic Lupus Erythematous Clinical, Immunological Manifestation and Damage Accrual. (15th July 2016) - Faria, R.; Dias, R.R.; Ferreira, R.; Pereira, P.G.; Inácio, I.; Leal, B.G.; Tavares, A.I.; Bettencourt, A.; Carvalho, C.; Almeida, I.; Marinho, A.; Martins da Silva, B.; et al.
Abstract : Background: Serotonin receptor 1A and 2A genes polymorphisms (HTR1A and HTR2A) have been associated to increased risk of depression and suicide. Hypomethylated HTR1A has been associated to Systemic Lupus Erythematosus (SLE) patients manifestations. Preliminary results in our cohort showed an association between HTR2A polymorphisms and SLE manifestations development risk and depression risk in SLE patients. Objectives: To investigate the association of 5-HTR2A polymorphisms (rs6314, rs6313) and clinical organ involvement, specific antibodies expression and damage accrual and time to damage accrual in SLE patients. Methods: 75 SLE patients were evaluated for 5-HTR2A polymorphisms rs6314 and rs6313, by a Taqman assay and PCR-RFLP methodology, respectively. SLE diagnosis was based in ACR 1999 criteria, the organic involvement and specific antibodies were reviewed in the charts (Cumulative SLE manifestations for genetic studies) and damage was assessed by SDI (Systemic Lupus International Collaborating Clinics - Damage Index). Statistical analysis was made with SPSS 22.0. Results: 75 SLE patients (70 female) with a mean age of diagnosis of 29.55 years old (SD 12.0) and mean follow-up time of 17, 39 years (SD 7, 70). Mucocutaneous involvement occurred in 88%, articular 85, 3%, renal 46, 7%, 30, 7% neuropsychiatric. 38 patients (50, 7%) had organ damage acrrual with a mean time to first damage accrual of 3, 75 years (SD 6, 88). 7 (9, 3%) accrued renal damage and 15 (20%) neuropsychiatric. Polymorphism distribution was rs6313 (CC 22, 7%, CT 54, 7% e TT 14, 7%) and rs 6314 (CC 86, 7%, CT 13, 3%). No association was found between these polymorphisms and any clinical involvement, cytopenias, antibodies, damage accrual or time to damage. Neuropsychiatric damage accrual was earlier in patients carrying CC rs6314. Conclusions: Contradictory results are a very common phenomena in studies of complex diseases mainly due to the interaction fo several genes. Although poorly studied the serotonin receptor and transporter genes have been linked to SLE development and depression in SLE patients. In our study, there was no relation between any clinical or serological manifestations and the rs6313 and rs6314 HTR2A polymorphism but the earlier neuropsychiatric damage accrual opens a window of doubt of what might be the role of serotonin in SLE heterogeneity. Disclosure of Interest: None declared